Crucified with the Crucified - about 108 blessed Polish martyrs - Rachwalik, walter (Studia Teologiczne Białystok Drohiczyn Łomża, 2023)
The time of warfare reveals both the cruelty of the occupying forces, resorting to sophisticated torture and rape outrage inflicting pain and death, and the heroism of the victims, who, in the face of falling suffering and the prospect of inevitable loss of life, maintain their human dignity. The above-mentioned, all-human experience was also reflected in the events of World War II (1939-1945), in the extreme opposing attitudes of the German criminals and the 108 blessed Polish martyrs.